Stereo-EEG based personalized multichannel transcranial direct current stimulation in drug-resistant epilepsy. (May 2022) - Daoud, Maëva; Salvador, Ricardo; El Youssef, Nada; Fierain, Alexane; Garnier, Elodie; Biagi, Maria Chiara; Medina Villalon, Samuel; Wendling, Fabrice; Benar, Christian; Ruffini, Giulio; Bartolomei, Fabrice
Highlights: We used personalized multichannel tDCS to target the epileptogenic zone identified by stereoelectroencephalography (SEEG). After 6 months with 3 cycles of 5 consecutive days of tDCS treatment (2 × 20 min per day), half of the patients were responders. The efficacy of tDCS in responders was associated to a significant decrease in functional connectivity measured from scalp EEG. Abstract: Objective: In epilepsy, multichannel transcranial direct electrical stimulation (tDCS) is applied to decrease cortical activity through the delivery of weak currents using several scalp electrodes. We investigated the long-term effects of personalized, multisession, stereotactic-EEG (SEEG)-targeted multichannel tDCS on seizure frequency (SF) and functional connectivity (Fc) as measured by EEG in patients with drug-resistant epilepsy (DRE). Methods: Ten patients suffering from DRE were recruited. Multichannel tDCS (Starstim, Neuroelectrics) was applied during three cycles (one cycle every 2 months) of stimulation. Each cycle consisted of five consecutive days where patients received tDCS daily in two 20 min sessions separated by 20 min. The montages were personalized to target epileptogenic area of each patient as defined by SEEG recordings. SF during and after treatment was compared with baseline. Fc changes were analysed using scalp EEG recordings. Results: After the last tDCS session, five patients experienced a SF decrease of 50% or more compared with baseline (R: responders, average SF decrease of 74%). We estimated Fc changes between cycles and across R and non-responder (NR) patients. R presented a significant decrease in Fc (p < 0.05) at the third session in alpha and beta frequency bands compared to the first one. Conclusions: Multichannel tDCS guided by SEEG is a promising therapeutic approach. Significant response was associated with a decrease of Fc after three stimulation cycles. Significance: Such results suggest that tDCS-induced functional plasticity changes that may underlie the clinical response.